Refractory Auto-Immune Thrombotic Thrombocytopenic Pupura Successfully Treated With Caplacizumab - Mellaza, Chloé; Henry, Nicolas; Fayolle, Pierre-Marie; Mortaza, Satar; Subra, Jean-François; Veyradier, Agnès; Coppo, Paul; Augusto, Jean-François (Frontiers in Medicine, 2020)
Thrombotic thrombocytopenic purpura (TTP) is a rare thrombotic microangiopathy characterized by mechanical hemolytic anemia, profound thrombocytopenia and neurological manifestations. Acquired auto-immune TTP, the most prevalent cause of TTP, is induced by the presence of inhibitory anti-ADAMTS13 auto-antibodies. Modern treatment of acquired TTP relies on plasma exchange (PE), rituximab (RTX) and steroids. Caplacizumab (Cablivi®), a humanized single-variable domain immunoglobulin that targets the A1 domain of the ultra-large vWF, inhibits the interaction between ultra-large vWF and platelets. In two clinical trials, caplacizumab in addition to conventional treatment allowed to shorten the delay to platelet count normalization in comparison to conventional treatment plus placebo, without increasing significantly hemorrhagic complications. Moreover, caplacizumab was associated with reduced occurrence of a secondary endpoint associating death, TTP recurrence and major thromboembolic events. Here, we report the off-label use of caplacizumab in a 68-year old patient with confirmed acquired TTP, severe thrombocytopenia and generalized tonic-clonic seizures requiring mechanical ventilation and admission in the intensive care unit. Conventional treatment was rapidly started. Despite intensification of PE treatment with twice daily sessions, steroids continuation and a second rituximab infusion at day 6, TMA worsened with thrombocytopenia at 21 G/L at D8 from admission. We also considered using caplacizumab, which we could obtain and start at day 12 from admission, as it was just being available under a temporary authorization use in France. As soon as 12 hours following caplacizumab initiation, we observed a significant increase of platelet count and improvement of other hemolytic parameters. We observed resolution of encephalopathy and complete recovery of motor paralysis, allowing to stop mechanical ventilation at day 14. Caplacizumab was maintained for 128 days until day 139 from initial admission. The patient is going well 10 months after initial admission, without any neurological sequalae and did not develop TTP relapse. Best to our knowledge, this is the first reported use of caplacizumab in such condition. This case report suggests that caplacizumab use may help reducing the rate of refractory TTP episodes.